Millets: A Key Player in Sustainable Food Systems - Leveraging the Year of Millets for Research and Development - Park, Sungyeon; Ágoston , Temesi (Acta Carolus Robertus, 2024)
The paper brings a general picture of millets in the world, where we face global challenges such as water shortage, land degradation, climate change, etc. Millet is recognized as a climate-resilient crop that can be beneficial to our environment and diversification of our diet besides main staples such as rice, corn, and wheat. For the recognition of these important components of millets, the United Nations declared the year 2023 as “the year of millets”, and FAO as the lead agency for celebrating the Year in collaboration with other stakeholders. The impact of this event clearly shows in the academic publication, in a broad term, academic research on millets thanks to its health and environmental benefits has grown exponentially led by India, China, the United States, and other countries. Scopus confirms this publication trend between 2000 2023 and VOS viewer bibliometric analysis reveals a prominent cluster connecting food security, climate change, and millet with other keywords. Although in Europe millets were planted for centuries ago, the consumption and production or even awareness of it have been relatively low, which means more research and development needs to be encouraged and the promotion of health and environmental benefits to consumers needs to be supported by the private and public sectors.